ACMEOLOGY OF THE MARITAL RELATIONSHIP - Raisa A. Zotova; Natalya G. Kulikova (Открытое образование (Москва), 2016)
As the basis of theoretical and practical studies leading psychological mechanisms of stability of the relations proposed noospheric vision of marriage. Considered noosferology promise for understanding the system of the marital relationship from the perspective of theory of the brain. Noospheric paradigm of social cognition is defined as an integrative phenomenon, studying holistic development of the individual, society, social groups in the context of macroevolution and psikhopedogogics